Aspectos intangíveis em ambientes de inovação do agronegócio - Souza, Luciane Silva de (2024)
Intangible aspects, even if not measured financially, are elements that are present in companies, even intrinsically, and tend to play an important role in the success of organizations. This success also happens in innovation environments, such as incubators, which aim for a more innovative process. Agribusiness startups are part of this process, with the aim of innovating this sector of the economy. Agribusiness innovations are capable of changing the landscape of agriculture, agro-industry and agricultural technology. For startups in this segment to be able to achieve the desired performance, it is important to identify variables that can be identified, evaluated, measured and monitored in the organizational context of these businesses. In this sense, considering the relevance of intangible aspects for innovation environments linked to agribusiness, the question is: how can intangible aspects in innovation environments in the agribusiness sector impact on management performance? The general objective of the study is to investigate intangible aspects in innovation environments in the agribusiness sector, highlighting their impact on managerial performance. The research is classified as applied, with an inductive method and a qualitative approach to the problem. In terms of objectives, this is an exploratory and descriptive study, with bibliographical research and data collection as the technical procedures, and the content analysis technique was used to analyze the data. The work was based, in the first stage, on a systematic literature review, considering published studies on innovation environments, agribusiness and managerial performance. The search for studies was restricted to the most respected databases, Scopus and Web of Science. The results point to various intangible aspects that can influence managerial performance. These aspects were classified into dimensions: (1) Intellectual (Intellectual Capital, Human Knowledge, Empathy, Behaviour, Self-confidence); (2) Organizational (Sustainability, Structural Capital, Motivation, Managerial Skills); and (3) Informational and Relationship (Innovation, Empathy, Leadership, Self-efficacy). Two research instruments were developed to compile the results: research instrument 1 was developed and validated with experts in the field of research and work related to the research topic, and research instrument 2 was developed based on the results of instrument 1 and applied to the managers of the startups. Through the research instruments, it was possible to identify that intangible aspects are relevant within the business and have a positive impact on the overall performance of agribusiness startups. Through the research instruments and the theoretical measurement model, the study presents all the links that lead to the results found. The contributions include the proposed theoretical measurement model, which refers to a hierarchical structure to support decision-making and can be a guide for managers to understand information that affects managerial performance. The strengthening of the literature and the perceptions of experts and managers lead to a practical contribution on the themes. In addition to adding value to the line of research in Controllership, the results are a signpost for identifying and paying attention to these intangible aspects.